Vinflunine for the treatment of non-small cell lung cancer. (1st December 2016) - Genova, C.; Alama, A.; Coco, S.; Rijavec, E.; Dal Bello, MG.; Vanni, I.; Biello, F.; Barletta, G.; Rossi, G.; Grossi, F.
ABSTRACT: Introduction : Vinflunine belongs to the class of vinca alkaloids and acts by disrupting the microtubule dynamics during cell cycle; this agent is currently available for previously treated advanced transitional cell carcinoma in Europe. The aim of this invited review is to evaluate the potential role of vinflunine for the treatment of non-small cell lung cancer (NSCLC). Areas covered : The potential role of vinflunine in NSCLC is discussed on the basis of the available data, including full papers and meeting abstracts. Relevant preclinical studies describing the pharmacological properties of vinflunine are also included. The review also summarizes clinical studies, including phase I trials involving NSCLC among other tumors as well as phase II/III trials specifically addressing this malignancy. Additionally, the safety profile and the current regulatory status of vinflunine is discussed. Expert opinion : Vinflunine is active as single agent and as part of platinum-based combinations in NSCLC. It results non-inferior to docetaxel in a randomized phase III trial including previously treated NSCLC patients; additionally, its safety profile is generally considered manageable. Ultimately, further studies are needed to confirm the role of vinflunine in NSCLC, in consideration of the evolving evidence regarding targeted therapies and immune check-point inhibitors.